Multiple immunity-related genes control susceptibility of Arabidopsis thaliana to the parasitic weed Phelipanche aegyptiaca - Christopher R. Clarke; So-Yon Park; Robert Tuosto; Xiaoyan Jia; Amanda Yoder; Jennifer Van Mullekom; James Westwood (PeerJ, 2020)
Parasitic weeds represent a major threat to agricultural production across the world. Little is known about which host genetic pathways determine compatibility for any host–parasitic plant interaction. We developed a quantitative assay to characterize the growth of the parasitic weed Phelipanche aegyptiaca on 46 mutant lines of the host plant Arabidopsis thaliana to identify host genes that are essential for susceptibility to the parasite. A. thaliana host plants with mutations in genes involved in jasmonic acid biosynthesis/signaling or the negative regulation of plant immunity were less susceptible to P. aegyptiaca parasitization. In contrast, A. thaliana plants with a mutant allele of the putative immunity hub gene Pfd6 were more susceptible to parasitization. Additionally, quantitative PCR revealed that P. aegyptiaca parasitization leads to transcriptional reprograming of several hormone signaling pathways. While most tested A. thaliana lines were fully susceptible to P. aegyptiaca parasitization, this work revealed several host genes essential for full susceptibility or resistance to parasitism. Altering these pathways may be a viable approach for limiting host plant susceptibility to parasitism.